Evaluation of biological activity of cellulose pulp by means of the static respiration index (AT4) = Ocena aktywności biologicznej pulpy celulozowej testem respiracyjnym AT(4) - Myszograj, Sylwia; Kozłowska, Katarzyna; Krochmal, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the countries of the European Union, work is presently being conducted on the standardisation of the limit values and test methods for the determination of the biological activity of waste. The aim of conducting the tests is to monitor the effectiveness of waste biodegradation during composting, the evaluate any decrease in the biological activity of the waste before its landfilling and control processes taking place at landfills.
Keywords: pulpa celulozowa; aktywność mikrobiologiczna; metodyka oznaczania; cellulose pulp; effectiveness of waste biodegradation; methods standardization